PROFIL GELATINISASI TEPUNG SORGUM PUTIH TERMODIFIKASI α-AMILASE - Endah Wulandari; Een Sukarminah; Efri Mardawati; Hanni Listia Furi (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2019)
Sorghum is potential to be developed into flour based products due its high starch content (around 80.42%). However, native sorghum flour is unstable during cooking, has low viscosity, and limited swelling power resulting in limited use in the industry. Starch in sorghum flour requires long cooking time and high cooking temperature, therefore modifications is needed to improve the properties of the sorghum starch. Enzymatic modification using α-amylase at (0, 200, 400, and 600 units/g) was selected. The results showed that modification using α-amylase of 200 units/g flour produced better characteristics of modified sorghum flour. The α-amylase modified flour has A type pattern of amylography, gelatinization temperature of 78.77°C, peak viscosity of 1266.67 BU, starch content of 48.41%, amylose content of 15.77%, and amylopectin content of 32.64%. The characteristics make the flour suitable for use in the manufacture of extrusion products.